Patterns of species richness in two African-centered, aridity-adapted flightless weevil lineages (Coleoptera: Curculionoidea) - Hickman, Taylor; Procheş, Şerban; Ramdhani, Syd (Zootaxa, 2017)
Weevils (Coleoptera: Curculionoidea) represent a remarkable proportion of global biodiversity, yet studies addressing their biogeography remain scarce. The arid parts of sub-Saharan Africa harbour several interesting weevil lineages, the most spectacular being the larger flightless weevils such as the Microcerinae and Brachycerus. Here we map the species richness of these two groups to identify hotspots in their diversity, and make inferences regarding the factors that may have contributed to the observed patterns. Exceptional richness values in both groups are found in southern Africa, and more specifically in the Nama Karoo, which is unremarkable in terms of plant diversity. By comparisons, plant diversity hotspots such as the Succulent Karoo and the Cape Floristic Region appear to have high, but not exceptional, weevil richness. Species richness levels were also high in the grassland and savanna areas of south-eastern Africa, which are not arid. The representation of genera considered here and their closest relatives, suggest an African origin for both lineages. This, combined with recent insights into weevil evolution, raise the possibility that advanced weevils as a whole (the family Curculionidae) originated in Africa and that some of its earliest offshoots survived and subsequently diversified here thanks to multiple factors, relating to climate and plant diversity alike.